Sonoporation of Cells by a Parallel Stable Cavitation Microbubble Array. Issue 17 (17th June 2019) - Meng, Long; Liu, Xiufang; Wang, Yuchen; Zhang, Wenjun; Zhou, Wei; Cai, Feiyan; Li, Fei; Wu, Junru; Xu, Lisheng; Niu, Lili; Zheng, Hairong
Abstract: Sonoporation is a targeted drug delivery technique that employs cavitation microbubbles to generate transient pores in the cell membrane, allowing foreign substances to enter cells by passing through the pores. Due to the broad size distribution of microbubbles, cavitation events appear to be a random process, making it difficult to achieve controllable and efficient sonoporation. In this work a technique is reported using a microfluidic device that enables in parallel modulation of membrane permeability by an oscillating microbubble array. Multirectangular channels of uniform size are created at the sidewall to generate an array of monodispersed microbubbles, which oscillate with almost the same amplitude and resonant frequency, ensuring homogeneous sonoporation with high efficacy. Stable harmonic and high harmonic signals emitted by individual oscillating microbubbles are detected by a laser Doppler vibrometer, which indicates stable cavitation occurred. Under the influence of the acoustic radiation forces induced by the oscillating microbubble, single cells can be trapped at an oscillating microbubble surface. The sonoporation of single cells is directly influenced by the individual oscillating microbubble. The parallel sonoporation of multiple cells is achieved with an efficiency of 96.6 ± 1.74% at an acoustic pressure as low as 41.7 kPa. Abstract : This work demonstrates a newly developed microfluidic device that enables parallel modulation of membrane permeability using an oscillating microbubble array. This parallel sonoporation device can generate an array of air microbubbles with the same diameter and the oscillation of the microbubble array is controllable.